1995
DOI: 10.1080/03079459508419105
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous viral genes influence infection with avian leukosis virus

Abstract: SUMMARYThe influence of endogenous viral (ev) genes on avian leukosis virus (ALV) infection was studied in ALV-free white leghorn chickens exposed to chicks from ALV shedding dams. The study included four lines, each segregating for one ev gene, one line free of ev genes, and four commercial stocks segregating for a number of ev genes. Genes ev12 and ev21 that produce the complete endogenous virus were associated with significant reductions in antibody response to ALV. In commercial stocks with ev21 in all bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For example, in the laboratory mouse endogenous proviruses occupy more than 0.5% of the cellular DNA (Pincus et al, 1992). On the contrary, the antigenic similarity between the products of the endogenous proviruses and the exogenous viral antigens reduces the ability of birds with certain types of these proviruses to mount an immune response against the exogenous virus (Crittenden et al, 1984;Gavora et al, 1995b). In the most thoroughly studied family of endogenous viral genes, there are more than 20 endogenous proviruses in various parts of the genome (Crittenden, 1991).…”
Section: Pathogen-mediated Resistancementioning
confidence: 99%
“…For example, in the laboratory mouse endogenous proviruses occupy more than 0.5% of the cellular DNA (Pincus et al, 1992). On the contrary, the antigenic similarity between the products of the endogenous proviruses and the exogenous viral antigens reduces the ability of birds with certain types of these proviruses to mount an immune response against the exogenous virus (Crittenden et al, 1984;Gavora et al, 1995b). In the most thoroughly studied family of endogenous viral genes, there are more than 20 endogenous proviruses in various parts of the genome (Crittenden, 1991).…”
Section: Pathogen-mediated Resistancementioning
confidence: 99%
“…In addition, ALVE elements have also been analyzed in other breeds (Gudkov et al, 1981), uncovering both novel proviruses as well as ones that had previously been identified in White Leghorns. Associations between ALVE elements and decreased immune response to exogenous avian leukosis virus (Gavora et al, 1995), as well as decreased egg production and egg weight (Gavora et al, 1991), have been reported. Moreover, the presence of ALVE elements in the chicken genome serves as a model system for understanding endogenous viruses in other vertebrates.…”
Section: Introductionmentioning
confidence: 97%
“…Endogenous ALVE are known to affect both infection by exogenous virus and disease progression Gavora et al, 1995) as well as host physiology in general. For example, ALVE loci that are transcriptionally active cause decreases in some economically important traits such as egg production, egg weight, and egg specific gravity (Gavora et al, 1991).…”
Section: Introductionmentioning
confidence: 99%